A Variety of Magnetism in CuMpt6 (M=3d Transition Metals) Ternary Alloys (Journal of Bangladesh Academy of Sciences, 2009)
The magnetic properties of polycrystalline CuMPt6 (M= Ti, V, Cr, Mn, Fe, Co and Ni) ternary alloys were studied by Superconducting Quantum Interference Device (SQUID) over the temperature range 4-300 K. Magnetization measurements revealed that the compounds containing M=Ti, V and Ni are paramagnetic. A spin glass type magnetic behavior appeared in the compounds with M= Cr and Mn in their annealed state and the corresponding temperatures for freezing the magnetic moments were Tg= 15 and 40 K, respectively. Positive values of the paramagnetic Curie temperature (Q) indicated that the ferromagnetic interaction is dominant in these spin-glass compounds. The compounds with M= Fe and Co showed ferromagnetic behavior having Curie temperatures (TC) = 230, and 190 K, respectively. Hysteresis study showed that the alloy with M=Co was magnetically softer than that with M=Fe. Keywords: CuMPt6 ternary alloys, Magnetic behavior, Effective magnetic moments (Peff), Spin glass type. doi: 10.3329/jbas.v32i2.2428 Journal of Bangladesh Academy of Sciences Vol.32(2) 2008 218-225